Application of Problem-based Learning Based Set Mobile Game Oriented to Motivation, Interest, and Logical-Mathematical Thinking - Nopi Tri Utami; Wahyu Setyaningrum (MASI Mandiri Edukasi, 2025)
The purpose of this study is to describe (1) the effectiveness of problem-based learning using Mobile Games; (2) the effectiveness of conventional learning using Mobile Games; and (3) the comparative effectiveness between problem-based learning using Mobile Games and conventional learning using Mobile Games in terms of students' motivation, interest, and logical-mathematical thinking ability. This research is a quasi-experimental study with a population of all seventh-grade students at SMP Negeri 1 Minggir, and the sample comprises classes VIIF and VIIG, each with 31 students. Data were obtained using non-test and test instruments. The effectiveness of mobile game treatment in each class was analyzed using t-tests and MANOVA (Hotteling T2). The results of this study show: (1) problem-based learning using Mobile Games is effective in terms of students' motivation, interest, and logical-mathematical thinking ability based on questionnaire and post-test; (2) conventional learning using Mobile Games is effective in terms of students' motivation, interest, and logical-mathematical thinking ability based on questionnaire and post-test; and (3) the results of the comparative effectiveness analysis show that problem-based learning using Mobile Games is more effective compared to conventional learning using Mobile Games in terms of students' motivation, interest, and logical-mathematical thinking.